New names in Heteropolygonatum (Asparagaceae) - Floden, Aaron Jennings (Phytotaxa, 2014)
Heteropolygonatum has been considered endemic to China, but molecular analyses and morphological observation of type and living collections necessitate the transfer of several Polygonatum to the former: Heteropolygonatum alternicirrhosum, H. anomalum, H. marmoratum, and H. parcefolium, which expands the range of the genus to neighboring Vietnam where H. marmoratum has been collected. Discussion of their morphology, perigone images, distribution, and full synonymy are given for the species transferred herein. Discussion of the distinctive generic morphology and karyotypes are provided in relation to their generic placement. Furthermore, the expansions of the provincial distributions of H. ginfushanicum and H. roseolum are given based on examination of herbarium material. A synoptic key to the genus is provided.